Religiusitas Dapat Menurunkan Tingkat Kecemasan Lansia di Masa Pandemi Covid-19 : Religiosity Can Reduce the Level of Anxiety in the Elderly During the Covid-19 Pandemic - Mury Prandika; Saiful Gunardi; Emi Yuliza (Journal of Nursing Education and Practice, 2022)
Introduction: Anxiety is an unpleasant feeling and generally causes physiological symptoms such as sweating, shaking, increased heart rate, etc., as well as psychological symptoms such as panic, tension, confusion, unable to concentrate, and so on. Objective: The purpose of this study was to determine the relationship between religiosity and the level of anxiety in the elderly during the COVID-19 pandemic at the Tebet District Health Center, South Jakarta. Methods: This study uses quantitative research methods. The population of this study was the elderly experiencing a level of anxiety during the COVID-19 pandemic at the Tebet sub-district health center. The sampling technique used was non-probability sampling. The total population in this study was 50 people. The instrument of this research used a questionnaire. The questionnaire used was a religious relationship questionnaire and an anxiety level questionnaire. This research uses chi-square analysis. Results: Based on the results of the chi-square test analysis, the value of = 0.05 > p value = 0.03. Conclusion: There is a relationship between religiosity and the level of anxiety in the elderly during the covid- 19 pandemic, at the Public Health Center, Tebet District, South Jakarta.